Attractiveness of Hotel Price Framing Methods for Thai Customers - Teerathongkum, Supawan; Sungkatavat, Sarinya (Journal of Business, Innovation and Sustainability (JBIS), 2023)
Domestic travel and accommodation businesses essentially drive Thailand’s economy. Pricing is a key factor that directly affects the number of hotel reservations and revenue. Due to the way price and deal information are presented, Price Framing Methods (PFM) could help attract customers and capture market demand. The purpose of this study is to examine the most attractive PFMs for Thai customers focusing on those frequently used by accommodation businesses and other related sectors. An online questionnaire survey was distributed to collect data for this study and 607 Thai customers responded. The results of descriptive statistics and Exploratory Factor, Analysis (EFA) reveal that the most attractive PFMs for Thai customers were “value for money deals” (M = 5.99, SD = 1.09), especially the “all-inclusive package” (M = 6.00, SD = 1.15) and “Buy one room get one room free” (M = 5.98, SD = 1.34), while “discount deals” (M = 5.59, SD = 1.17) were also popular. The findings of this research will help accommodation businesses to develop strategic PFMs to attract Thai customers and generate incremental revenue.